Heavy metal driven co-selection of antibiotic resistance in soil and water bodies impacted by agriculture and aquaculture - Seiler, Claudia; Berendonk, Thomas U. (Frontiers in Microbiology, 2012)
The use of antibiotic agents as growth promoters was banned in animal husbandry to prevent the selection and spread of antibiotic resistance. However, in addition to antibiotic agents, heavy metals used in animal farming and aquaculture might promote the spread of antibiotic resistance via co-selection. To investigate which heavy metals are likely to co-select for antibiotic resistance in soil and water, the available data on heavy metal pollution, heavy metal toxicity, heavy metal tolerance and co-selection mechanisms was reviewed. Additionally, the risk of metal driven co-selection of antibiotic resistance in the environment was assessed based on heavy metal concentrations that potentially induce this co-selection process. Analyses of the data indicate that agricultural and aquacultural practices represent major sources of soil and water contamination with moderately to highly toxic metals such as copper (Cu) and zinc (Zn). If those metals reach the environment and accumulate to selective concentrations they can trigger co-selection of antibiotic resistance. Furthermore, co-selection mechanisms for these heavy metals and clinically as well as veterinary relevant antibiotics have been described. Therefore, studies investigating co-selection in environments impacted by agriculture and aquaculture should focus on Cu and Zn as selecting heavy metals. Furthermore, results of the general selection mechanisms need to be carefully evaluated and the respective environmental background has to be taken into account.